(untitled) (Revista Lusófona de Educação, 2023)
The key claim of the article is that the Covid pandemic has offered museums important new opportunities to foster more, and more diverse, citizen engagements; and such engagements may be key to sustainable museum innovation in the future. The claims are underpinned by first mapping the characteristics of two leading paradigms in existing museum interaction with the world: a technology paradigm and a personalisation paradigm. Second, the article provides three empirical examples on how museums may apply participatory designs to foster more inclusive and diverse citizen engagements. The examples are based on case studies conducted at a Danish R&D programme, Our Museum. By way of conclusion, it is discussed how and why citizen engagements can catalyse sustainable museum innovation. Key words: museum personalization; museum technology; citizen engagement